2008
DOI: 10.1017/s1740925x09990159
|View full text |Cite
|
Sign up to set email alerts
|

N-methyl-d-aspartate receptor independent changes in expression of polysialic acid-neural cell adhesion molecule despite blockade of homosynaptic long-term potentiation and heterosynaptic long-term depression in the awake freely behaving rat dentate gyrus

Abstract: N-methyl-D-aspartate receptor independent changes in expression of polysialic acid-neural cell adhesion molecule despite blockade of homosynaptic long-term potentiation and heterosynaptic long-term depression in the awake freely behaving rat dentate gyrus j. j. rodri 'guez 1,2 * , g. m. dalle ' rac 3 * , m. tabuchi 1 , h. a. davies 4 , f. m. colyer 4 , m. g. stewart 4 and v. doye ' re 3 Investigations examining the role of polysialic acid (PSA) on the neural cell adhesion molecule (NCAM) in synaptic plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…They suggested that this rapid response resulted from release from large dense‐core vesicles rich in PSA‐NCAM. An alternative explanation can be found in the work of Rodríguez and co‐workers41, who reported a rapid increase (within 10 min) of mRNA levels encoding the sialyltransferase enzymes in rat dentate gyrus following LTP induction.…”
Section: Discussionmentioning
confidence: 97%
“…They suggested that this rapid response resulted from release from large dense‐core vesicles rich in PSA‐NCAM. An alternative explanation can be found in the work of Rodríguez and co‐workers41, who reported a rapid increase (within 10 min) of mRNA levels encoding the sialyltransferase enzymes in rat dentate gyrus following LTP induction.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown PSA-NCAM is essential in the activity-dependent induction of hippocampal LTP and LTD [35], where the polysialylation of NCAM is positively correlated with neural activity of glutamatergic neurons [120, 121]. Moreover, inhibiting the polysialylation of NCAM reduces the rate of dendritic spine formation and decreases the stability of these spines [122].…”
Section: Potential Role For Psa-ncam In Antidepressant Efficacymentioning
confidence: 99%
“…To further investigate the role of neuronal activity on Fz5 localization, we examined the effect of patterned electrical stimulation, shown to regulate the distribution of a number of receptors (Du et al, 2000;Hayashi et al, 2000;Rodriguez et al, 2008;Shi et al, 1999). We used two different electrical stimuli to induce neuronal activity.…”
Section: Different Patterns Of Electrical Stimulation Differentially mentioning
confidence: 99%